Structural Basis for Genetic-Code Expansion with Bulky Lysine Derivatives by an Engineered Pyrrolysyl-tRNA Synthetase. Issue 7 (18th July 2019) - Yanagisawa, Tatsuo; Kuratani, Mitsuo; Seki, Eiko; Hino, Nobumasa; Sakamoto, Kensaku; Yokoyama, Shigeyuki
Summary: Pyrrolysyl-tRNA synthetase (PylRS) and tRNA Pyl have been extensively used for genetic-code expansion. A Methanosarcina mazei PylRS mutant bearing the Y306A and Y384F mutations (PylRS(Y306A/Y384F)) encodes various bulky non-natural lysine derivatives by UAG. In this study, we examined how PylRS(Y306A/Y384F) recognizes many amino acids. Among 17 non-natural lysine derivatives, N ɛ -(benzyloxycarbonyl)lysine (ZLys) and 10 ortho/meta/para -substituted ZLys derivatives were efficiently ligated to tRNA Pyl and were incorporated into proteins by PylRS(Y306A/Y384F). We determined crystal structures of 14 non-natural lysine derivatives bound to the PylRS(Y306A/Y384F) catalytic fragment. The meta - and para -substituted ZLys derivatives are snugly accommodated in the productive mode. In contrast, ZLys and the unsubstituted or ortho -substituted ZLys derivatives exhibited an alternative binding mode in addition to the productive mode. PylRS(Y306A/Y384F) displayed a high aminoacylation rate for ZLys, indicating that the double-binding mode minimally affects aminoacylation. These precise substrate recognition mechanisms by PylRS(Y306A/Y384F) may facilitate the structure-based design of novel non-natural amino acids. Graphical Abstract: Highlights: A mutant pyrrolysyl-tRNA synthetase, PylRS(Y306A/Y384), acts on diverse amino acids The PylRS mutant and tRNA Pyl incorporated 17 non-natural amino acids into proteins Crystal structures of the PylRS mutant bound with 14 of the amino acids were solved This information will facilitate the structure-based design of novel amino acids Abstract : Yanagisawa et al. analyzed the Y306A/Y384F mutant of Methanosarcina mazei pyrrolysyl-tRNA synthetase (PylRS) with 17 non-natural, bulky oxycarbonyllysine derivatives for tRNA Pyl aminoacylation and site-specific incorporation into proteins. Fourteen crystal structures of the amino acid-bound PylRS mutant revealed the structural bases of the binding. This information facilitates the structure-based design of novel amino acids.